Suru Maca: Tradisi Menyambut Bulan Ramadan Masyarakat Desa Pakkabba Kabupaten Takalar Sulawesi Selatan - Abdul Rahman; Muhammad Syukur; Abdul Aziz (Balai Penelitian dan Pengembangan Agama Semarang, 2020)
The suru maca ritual is a tradition of the Islamic community of Pakkabba Village in Takalar Regency, South Sulawesi province, to welcome Ramadan's arrival. At present, the implementation of this tradition is enjoyed by local communities and enjoyed by immigrant communities of different ethnicities and religions. This tradition is alive and well in society because it is functional and has a significant symbolic meaning for this culture's owner. This study aims to determine the purpose and function of the suru maca ritual for Pakkabba Village people. This research is a qualitative study that uses an ethnographic approach. Data was collected through literature review, participatory observation, and in-depth interviews. Data were analyzed using a functional, structural approach. The results showed that the existence of Islam had been accepted and became part of the Pakkabba village community's social system so that the month of Ramadan, which is the holy month of Muslims, is expressed through the local tradition of suru maca. The suru maca ritual means a communicative act and is an arena of women's power. At the same time, its functions include expressing feelings, strengthening solidarity, strengthening kinship relationships, moral renewing, and maintaining identity